Efficacy of the Super-Retinal Imaging Display Based on Scanning Laser Technology in Visual Impairment Induced by Corneal Diseases - Fujimoto, Hisataka; Kiryu, Junichi (Journal of Ophthalmology and Research, 2021)
We investigated the effectiveness of wearable laser-eyewear (LEW) in visual impairment owing to corneal disease, including low vision (LV) eye. LEW was performed in 35 patients (38 eyes) with irregular corneal astigmatism. Best corrected visual acuity (BCVA) and visual acuity (VA) with LEW were measured using Landolt rings. Corneal topography was measured using anterior segment optical coherence tomography; corneal opacity grade was observed using slit lamp examination. A significant negative correlation between Logarithm of the Minimum Angle of Resolution (LogMAR) VA improvement using LEW and basal BCVA was observed. In 20 eyes of the LV, no significant correlation was observed between VA improvement by LEW and basal BCVA. The LogMAR VA improvement using LEW was 0.27±0.32 (-0.48−0.70) in ×1 0.53±0.37 (-0.17−1.18) in ×2. The most significant factor that determined VA improvement in eyes with LV using LEW was the corneal opacity grade, while the corneal topographic parameters, including keratometric refractive parameters (Kmax, Ks, Kf, and Cylinder), higher-order aberrations (HOAs), and central corneal thickness (CCT), showed no or limited impact on the VA improvement effect by LEW in LV. Therefore, LEW improves vision regardless of irregular corneal astigmatism; however, corneal opacity limits the LEW effect in the LV eye.